Shakespeare's dramatic transactions - Mooney, Michael E., 1947- (E-Duke books scholarly collection., 1990)
Shakespeare's Dramatic Transactions uses conventions of performance criticism-staging and theatrical presentation-to analyze seven major Shakespearean tragedies: Hamlet, Othello, King Lear, Macbeth, Antony and Cleopatra, Richard II, and Richard III. As scholars and readers increasingly question the theoretical models used to describe the concepts of "mimesis" and "representation," this book describes how the actor's stage presentation affects the actor's representational role and the ways in which viewers experience Shakespearean tragedy. Michael Mooney draws on the work of East German critic R